Meccan Fatwas from the End of the Nineteenth Century on Indonesian Affairs - Kaptein, Nico (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1995)
Centuries of Indonesian Muslims turned into Arabic to obtain fatwas they need on various religious issues that arise in the homeland. Among the books that contain these fatwas are Muhimmat al-bayan fi nafa'is as'ilat al-Hadith. This is a fatwa issued by the mufti-mufti of Mecca, especially at the end of the nineteenth century at the request of the Muslims in the archipelago.In the book contained a fatwa related to the attitude to be taken over the archipelago Muslims who reject the Dutch colonial government. In the fatwa colonial government itself was not challenged, and the colonial government implicitly recognized that infidels should. This fatwa is quite different from the views circulating in Aceh, where local clerics called for jihad against the infidel invaders. Saudi Fatwa of Mufti is expected to come to relieve the situation in Aceh.DOI: 10.15408/sdi.v2i4.824